Performance Level of Physical Education Students: Basis for the Development of Task-Based Teaching Strategies - Limbo, Abegail B.; Limbo-Rivera, Charis B. (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. In teaching Physical Education (PE), one must have a repertoire of suitable teaching strategies to facilitate learners’ competencies. Thus, this study aims to determine the performance level of the Grade 10 PE students and the extent of implementation of the Grade 10 PE curriculum in Mahaplag, Leyte Division, with the end view of designing a task-based teaching strategy in Physical Education. Materials and methods. This research utilized a descriptive survey research method involving six hundred sixty (660) Grade 10 students, six (6) PE teachers, six (6) department heads and coordinators, and two (2) school heads categorized as principals of the respondent schools employing total population. The study used an achievement test and a self-structured questionnaire with 5-point scale responses to gather the needed data. Results. Results revealed an average performance level of students in PE; the content learning areas were satisfactorily undertaken; the performance standards were satisfactorily developed; the teaching and learning strategies were sometimes utilized; and the instructional procedures on experiential learning activities were sometimes undertaken. These findings highlight teachers’ need to enhance the delivery of content learning areas and diversify teaching strategies in implementing the Grade 10 PE curriculum. Conclusions. The study underscores the potential of task-based teaching strategies to foster student engagement and improve performance outcomes in physical education, suggesting further research into innovative pedagogical approaches.